In vitro propagation of pointed gourd (Trichosanthes dioica Roxb.) through encapsulated shoot tips (Bangladesh Journal of Agricultural Research, 2010)
Plants were regenerated from encapsulated shoot tips of pointed gourd. Shoot tips isolated from multiple shoot cultures of AM-8 and AM-15 cultivars of pointed gourd were encapsulated in sodium alginate beads. For germination and shoot proliferation, encapsulated shoot tips (artificial seed) were cultured in MS basal medium containing different concentrations and combinations of BAP and NAA. Use of MS medium resulted in 90% conversion of encapsulated shoot tips into plantlets. The results exhibited that BAP and combinations of BAP and NAA play an important role in germination of artificial seed being encapsulated by sodium alginate beads. The plantlets were successfully established in earthen pot. Under the present study, limited experimental efforts have been made to establish the protocol for encapsulating the shoot tips for the production of artificial seed and their subsequent regeneration. It is the first report in Bangladesh in developing artificial seed production technique using vegetative tissue of pointed gourd. Key Words: In vitro propagation; pointed gourd; shoot tips. DOI: 10.3329/bjar.v34i4.5832Bangladesh J. Agril. Res. 34(4) : 555-563, December 2009